2015
DOI: 10.1093/mutage/geu030
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Pig-a mutation in flow cytometry-identified CD48-deficient T-lymphocytes from F344 rats

Abstract: The Pig-a assay is used for monitoring somatic cell mutation in laboratory animals and humans. The assay detects haematopoietic cells deficient in glycosylphosphatidylinositol (GPI)-anchored protein surface markers using flow cytometry. However, given that synthesis of the protein markers (and the expression of their genes) is independent of the expression of the X-linked Pig-a gene and the function of its enzyme product, the deficiency of markers at the surface of the cells may be caused by a number of events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 17 publications
3
44
0
Order By: Relevance
“…Individual CD48‐deficient T‐cells were sorted using a flow cytometer into culture medium for clonal expansion and subsequent molecular analysis of Pig‐a mutation. We found that the spectrum of Pig‐a mutations in CD48‐deficient T‐cells derived from DMBA‐treated rats was different from the spectrum of Pig‐a mutations in ENU‐treated rats—the former was dominated by A→T transversions, whereas the latter was dominated by T→A transversions [Revollo et al, ]. The nature of the basepair substitutions is consistent with the types of DNA damage produced by the two agents (adducts with dA vs. adducts with dT).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Individual CD48‐deficient T‐cells were sorted using a flow cytometer into culture medium for clonal expansion and subsequent molecular analysis of Pig‐a mutation. We found that the spectrum of Pig‐a mutations in CD48‐deficient T‐cells derived from DMBA‐treated rats was different from the spectrum of Pig‐a mutations in ENU‐treated rats—the former was dominated by A→T transversions, whereas the latter was dominated by T→A transversions [Revollo et al, ]. The nature of the basepair substitutions is consistent with the types of DNA damage produced by the two agents (adducts with dA vs. adducts with dT).…”
Section: Discussionmentioning
confidence: 74%
“…The relative fraction of the mutant genotype clones is superimposed on the averaged absolute frequency of CD48‐deficient (presumed Pig‐a mutant) T‐cells determined in vehicle‐control and mutagen‐treated F344 male rats. An asterisk represents the data that were reported in an earlier study [Revollo et al, ]. The frequency of clones with WT Pig‐a genotype (false mutant clones) is small relative to the frequency of true Pig‐a mutant clones in ENU‐ and DMBA‐treated rats.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For instance, in the case of rat erythrocytes, fluorochrome‐conjugated antibodies against the GPI‐anchored antigen CD59, together with flow cytometric analysis, are used to score the incidence of nonfluorescent mutant cells relative to fluorescent wild‐type cells. DNA‐sequencing results clearly support the use of the GPI anchor‐deficient phenotype as a reliable reporter of Pig‐a gene mutation (Kimoto et al, ; Dobrovolsky et al, ; Nicklas et al, ; Revollo et al, , ; Krüger et al, ; Bemis et al, ).…”
Section: Introductionmentioning
confidence: 84%